2020
DOI: 10.2172/1607754
|View full text |Cite
|
Sign up to set email alerts
|

Herbaceous Feedstock 2019 State of Technology Report

Abstract: The U.S. Department of Energy (DOE) promotes the production of advanced liquid transportation fuels from lignocellulosic biomass by funding fundamental and applied research that advances the State of Technology (SOT). As part of its involvement with this mission, Idaho National Laboratory (INL) completes an annual SOT report for biomass feedstock logistics. This report summarizes supply system impacts of Bioenergy Technologies Office (BETO)-funded research and development efforts at INL and elsewhere (such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…The US Department of Energy's delivered feedstock cost targets have ranged from $79-$93 Mg −1 ($71-$84 ton −1 ). 8,20,42,43 However, cost targets vary by feedstock mix and quality specifications. Actual feedstock cost targets will be influenced by market pull and policy for decarbonization with different products and conversion costs, which are unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The US Department of Energy's delivered feedstock cost targets have ranged from $79-$93 Mg −1 ($71-$84 ton −1 ). 8,20,42,43 However, cost targets vary by feedstock mix and quality specifications. Actual feedstock cost targets will be influenced by market pull and policy for decarbonization with different products and conversion costs, which are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The US Department of Energy's delivered feedstock cost targets have ranged from $79–$93 Mg −1 ($71–$84 ton −1 ) 8,20,42,43 . However, cost targets vary by feedstock mix and quality specifications.…”
Section: Discussionmentioning
confidence: 99%
“…Although the switchgrass grower payment in the 2018 Herbaceous Feedstock State of Technology (SOT) report (Roni et al, 2018) is reported as $38.87, it was decided to use a more aggressive cost target of $26.66, the same cost associated with three-pass corn stover. In the 2019 SOT report, ILM strategies were incorporated to reduce biomass access costs by 20% and to increase biomass availabilities in Kansas, Nebraska and Colorado (Roni et al, 2019). The analysis results implied that even with the 20% reduced cost previously demonstrated in the 2018 TEA, switchgrass was not cost-competitive to be included into the feedstock blend, which suggested that 20% might not be a low-enough cost reduction target.…”
Section: Methods Briefmentioning
confidence: 99%
“…The transportation distance was assumed to be similar to what was used in a two-pass harvest baled logistics system. 28 On-site preprocessing at the biorefinery involved unloading the silage tube using the walking floor trailer, and plastic wrap removal that was facilitated by a high tonnage knuckle boom. The wrap used was assumed to be collected and disposed of in a local landfill.…”
Section: Techno-economic Assumptionsmentioning
confidence: 99%
“…The assumed grower payment for corn stover residues was based on a two-pass corn stover harvest and collection approach representing the state of technology within the context of bioenergy production. 28 Fixed costs or all unit operations included capital recovery, insurance, and taxes, and were estimated following the guidelines published by American Society of Agricultural and Biological Engineers (ASABE). A list of all equipment used in this scenario is presented in Table 2, along with machine purchase price, machine life, and salvage value.…”
Section: Cost Basismentioning
confidence: 99%